The role of experience in proving electronic transactions and the technical rules governing them in the discovery of digital evidence - Mebarkia, Taki; Gheribi, Fatima zohra (Journal of Human Sciences, 2022)
The technical development of the automated processing systems has resulted in a major change in the prevailing concepts of evidence, and in fact such a statement has led to a growing role of scientific proof and the announcement of the joining of technical expertise in the world of judicial experience. The fact that digital evidence required to prove and expose informational crimes is something of a concern for experts in this field, and it is inconceivable that a judge will refuse to resort to the sendacement of an expert in information technology cases, as they are technical cases requiring special expertise. His judgment is contrary to scientific logic and flawed if it is not based on technical expertise in this field in order to achieve an important principle of specialization.